304 grade ultra-high strength, high plasticity, wear-resistant stainless steel with pitting resistance and manufacturing method thereof
By adopting specific chemical components and Mo-N-Nb alloying design in ultra-high strength stainless steel, combined with the formation of reverse austenite, the problem of insufficient corrosion resistance in the prior art is solved, and the 304-level pitting resistance is achieved The performance and high strength and high plasticity effects reduce production costs and manufacturing difficulties.
Patent Information
- Application Number
- CN202411435471.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-15
AI Technical Summary
Existing ultra-high strength stainless steels have insufficient corrosion resistance in highly corrosive environments, resulting in increased wear and failure, and high cost and complex manufacturing processes are difficult to apply on a large scale.
Ultra-high strength, high plastic wear-resistant stainless steel with grade 304 resistance to pitting, its chemical composition is designed in specific proportions, including C, Si, Mn, Cr, Ni, Mo, N, Nb and other elements, and is alloyed by Mo-N-Nb Design and specific heat treatment processes to form reverse transform austenite, improving pitting and mechanical properties.
Achieve 304-level pitting resistance, the pitting potential is higher than 250mV, the pitting corrosion rate is lower than 10 g/(m2*h), the yield strength Rp0.2≥950MPa, the elongation EL≥15%, the hardness ≥420HBW, which reduces It has cost and manufacturing difficulty, and is suitable for high corrosion environments.
Smart Images

Figure CN118932250B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of martensitic stainless steel, and in particular to a 304-grade ultra-high-strength, high-plasticity, wear-resistant stainless steel with pitting corrosion resistance and a manufacturing method thereof. Background Art
[0002] With the development of strategic emerging industries such as new materials, new equipment, and new generation information technology, the requirements for stainless steel quality and performance are constantly increasing. High strength, high corrosion resistance, and long life have become the main strategic development direction of stainless steel products. The stainless steel industry is an industrial industry with large carbon emissions. Green and low-carbon development has become the core proposition of the transformation and development of the stainless steel industry, and it is also the only way for the stainless steel industry to achieve high-quality development. By improving the performance of stainless steel products, extending the service life, and improving the mechanical properties of stainless steel products, the method of "replacing coarse with fine, thick with thin, and heavy with light" is adopted. Under the premise of not reducing product quality, the use of steel can be reduced by high strengthening. Using high-strength steel instead of ordinary steel in the automotive industry can not only reduce the use of steel, but also reduce vehicle fuel consumption and achieve low-carbon emissions for the entire industry chain.
[0003] According to the strength level classification, the yield strength above 355MPa is usually called high-strength steel, and above 960MPa is ultra-high-strength steel. The yield strength of existing ultra-high-strength carbon steel is about 1000MPa, which is widely used in the field of engineering machinery, such as wear-resistant car hoods, crane booms, heavy-duty truck chassis, etc. Its elongation is generally around 12%. In highly corrosive environments such as industrial areas, humid atmospheres and mines, it has insufficient corrosion resistance, resulting in corrosion and corrosion-intensified wear and failure. This requires a good combination of ultra-high strength and corrosion resistance, that is, ultra-high-strength stainless steel. In the field of engineering machinery, improving the corrosion resistance and wear resistance of stainless steel, slowing down corrosion and wear failure in service, and increasing the product life cycle, thereby reducing carbon emissions throughout the life cycle. In the next few decades, new stainless steel materials with high strength, high corrosion resistance and high wear resistance will replace existing traditional stainless steel and high-strength carbon steel and have a broader application prospect.
[0004] Chinese patent number CN200610147771.9 discloses "strong and tough ultra-high strength stainless steel and its manufacturing method", and its composition design (wt%) is C 0.05~0.13, Mn≤0.10, Si≤0.10, S≤0.002, P≤0.006, Cr 12.0~14.0, Ni 2.0~6.0, Co 11.0~13.0, Mo 3.5~5.5, V 0.15~0.25, Nb≤0.15, W 0.8~1.2, N≤0.005, Fe and unavoidable impurities. It is smelted in a vacuum induction furnace and a vacuum consumable furnace, and then forged and upset to make the finished product, with a tensile strength of 1800MPa, a yield strength of 1400MPa, and an elongation greater than 11%.
[0005] Chinese patent number CN201210091503.5 discloses "a method for manufacturing ultra-high strength stainless steel with good plasticity and toughness", and its composition design (wt%) is C 0.16~0.32; Si≤0.1; Mn≤0.1; Cr10.0~15.0; Ni6.0~8.0; Co13.0~16.0; Mo1.0~3.0; W0.9~1.1; V0.2~0.5; Nb0.08~0.15; N≤0.002; O≤0.0015, and the rest is Fe and unavoidable impurities. By adopting double vacuum melting, large forging ratio forming technology and deep cold heat treatment technology, the tensile strength reaches 1900MPa, the yield strength reaches 1500MPa, and the elongation is greater than 11%.
[0006] Chinese patent number CN 202410406826.1 discloses "a wear-resistant stainless steel and its preparation method and parts", whose composition design (wt%) is C0.4-0.6; Si0.1-0.3; Mn1.0-1.2; Cr 14.5-16.0; Mo 2.5-3.8; W 1.2-1.8; V 0.6-0.8; Ce 0.02-0.08; N≤0.5; Cu≤0.5; Ni≤0.5; Ti≤0.01; S≤0.02, and Fe and unavoidable impurities. Through electroslag remelting, forging, annealing, hot rolling, annealing, quenching, deep cryogenic treatment and tempering heat treatment. The finished product hardness ≥52HRC, yield strength ≥1300Mpa.
[0007] The above patented products have excellent performance, but the cost is high due to the addition of large amounts of precious metals such as Co and Mo, the addition of refractory metal W, and ultra-low temperature deep cold heat treatment, which makes the manufacturing difficult and costly, making it difficult to apply on a large scale.
[0008] Existing 1000MPa grade ultra-high strength stainless steel usually adds expensive metal elements such as Co-Ni-Mo, and is a maraging steel with excellent mechanical and corrosion resistance. However, the alloy is expensive, the manufacturing process is complex, the welding process requirements are strict, and the welding performance is poor, making it difficult to use in engineering machinery and other fields. Summary of the invention
[0009] The present invention aims to provide a 304 grade ultra-high strength, high plasticity, wear-resistant stainless steel with pitting resistance and a manufacturing method thereof, wherein the stainless steel has a corrosion resistance of 304 grade and a wear resistance better than Hardox450, and the yield strength Rp0.2 of the stainless steel is ≥950MPa, the elongation EL is ≥15%, the hardness is ≥420HBW, the pitting potential is ≥250mV, and the pitting rate is ≤10 g / (m 2 *h); can be used in energy coal, mining transportation, urban dredging and other environments with both wear and corrosion.
[0010] To achieve the above purpose, the technical solution of the present invention is as follows:
[0011] 304 grade ultra-high strength, high plasticity and wear-resistant stainless steel with pitting resistance, its chemical composition mass percentage is:
[0012] C: 0.03~0.15%,
[0013] Si: 0.25~1.0%,
[0014] Mn: 1.0~3.0%,
[0015] Cr: 14.0~16.0%,
[0016] Ni: 3.0~5.0%,
[0017] Mo: 0.5~1.5%,
[0018] N: 0.05~0.15%,
[0019] Nb: 0.01~0.1%,
[0020] P≤0.045%,
[0021] S≤0.0020%,
[0022] The balance includes Fe and other unavoidable impurities, and the following relationship must be satisfied at the same time:
[0023] Pitting resistance equivalent PREN (Nb) ≥ 19.0,
[0024] Pitting resistance equivalent PREN-Nb=Cr+3.3Mo+16N+Nb;
[0025] 20%≤Reverse transformation austenite content RA≤35%,
[0026] RA=110C+67N+2.75Ni+1.58Ni 2 -16.8Mn +4.3Mn 2 -5.6Mo-6.65, unit, volume percentage;
[0027] 400℃≤Martensite transformation Ms≤500℃,
[0028] Ms=1050-301(C+N)-33.3Mn-28Cr-16.7Ni-11.1(Mo+Si)-35×Nb, unit, ℃.
[0029] Furthermore, the chemical composition of the stainless steel also includes one or more of: V≤0.2%, B≤0.0050%, and Ca≤0.0050%, in percentage by mass.
[0030] Furthermore, the balance is Fe and other inevitable impurities.
[0031] The stainless steel of the present invention has a yield strength Rp0.2 ≥ 950 MPa, an elongation EL ≥ 15%, a hardness ≥ 420 HBW, a pitting potential ≥ 250 mV, and a pitting rate ≤ 10 g / (m 2 *h).
[0032] In the composition design of the ultra-high strength, high plasticity, wear-resistant stainless steel of the present invention:
[0033] C: A higher C content will increase the strength of the steel, but the plasticity and weldability will decrease. In order to ensure that the microalloyed steel has good welding performance, a low carbon content should generally be used. However, for high-strength low-alloy steel, if the C content is too low (<0.03%), it is difficult to obtain a martensitic structure, and its strength is reduced. Therefore, the C content of the present invention is controlled between 0.03% and 0.15%.
[0034] In addition, C can also be used in microalloyed steel
[0035] It forms a variety of second phase particles, such as MC, M2C and other precipitates with Cr, and fine dispersed nano-scale precipitates with V, Nb and T. These precipitated second phase particles can play a role in grain refinement and precipitation strengthening. C has a good effect on stabilizing retained austenite, can expand the austenite zone, delay the transformation of ferrite and bainite, and reduce the martensite transformation temperature.
[0036] Si: It is beneficial to improve the oxidation resistance of stainless steel, but too high a content will significantly reduce the plasticity of stainless steel. Too high a silicon content will increase the ferrite content, reduce the nitrogen solubility of the material, and also reduce the solid solubility of C in austenite, promoting Cr 23 C6 precipitates at the grain boundary. Therefore, the Si content of the present invention is controlled at 0.25-1.0%.
[0037] Mn: Mn is one of the representative austenite stabilizing elements, which can expand the austenite zone and is beneficial to the production of microalloyed steel hot rolling process. Mn can improve the hardenability of steel plates and reduce the precipitation temperature of carbides. At the same time, the Mn element can reduce the activity of C and N elements in ferrite and austenite, and increase the solid solubility of N element in ferrite. The ability of Mn to stabilize the austenite structure in steel is second only to Ni, and it is an element that strongly improves the hardenability of steel. Therefore, in martensitic stainless steel, Mn can partially replace Ni. However, the addition of Mn will reduce the corrosion resistance of stainless steel. The Mn content of the present invention is controlled at 1.0~3.0%.
[0038] Cr: Cr is the main alloying element of stainless steel and plays a decisive role in corrosion resistance. In oxidizing media, Cr can form Cr2O3 on the surface of steel, a stable and dense protective film, thereby producing a passivation effect to prevent further corrosion of the steel. Its corrosion resistance changes in a leap-forward manner according to the n / 8 law. As the Cr content increases, the corrosion resistance of stainless steel in oxidizing media increases accordingly. Cr can effectively increase the pitting potential value of steel and reduce the sensitivity of steel to pitting corrosion. Therefore, Cr is an indispensable alloying element in martensitic aging stainless steel. When Cr is used in combination with Mo, the anti-pitting effect is better. Cr is a strong ferrite-forming element and an element that reduces the austenite zone. For martensitic aging stainless steel, the Cr content is generally 10.5%~18% (mass fraction). If the Cr content is too high, the full martensitic structure (containing part of the ferrite structure) will not be obtained after solution treatment, and the presence of ferrite will affect the thermoplasticity of the steel, reduce the strength of the steel, and deteriorate the transverse toughness and corrosion resistance of the steel. On the other hand, Cr is an element that reduces Ms, and therefore, the Cr content of the present invention is controlled within a range of 14.0% to 16.0%.
[0039] Ni: Ni is also an indispensable element in martensitic aging stainless steel. It can improve the potential and passivation tendency of stainless steel, and can also improve the cavitation resistance and soil corrosion resistance of martensitic stainless steel. Ni can improve the plasticity and toughness of steel, especially the toughness at ultra-low temperatures, which is related to its property of reducing the interaction energy between dislocations and interstitial atoms. In order to ensure that the austenitic structure at 815~1100°C is completely transformed into a martensitic structure after cooling to room temperature, the Ni content in martensitic aging stainless steel should be 4%~20% (mass fraction), but Ni will also reduce Ms, and the effect is stronger than Cr. If the Ni content is too much, Ms will be reduced, causing the steel to lose its quenching ability, and will lead to the formation of residual austenite during cooling, so that the full martensitic structure cannot be obtained, which reduces the strength after aging. Therefore, the Ni content of the present invention is controlled at 3%~5%.
[0040] Mo: It is beneficial to the strength, toughness and corrosion resistance of martensitic stainless steel. The presence of alloying element Mo in martensitic stainless steel can also prevent the precipitation phase from precipitating along the original austenite grain boundary, thereby avoiding intergranular cracking and improving fracture toughness. Mo can increase the tempering stability and secondary hardening effect, and improve the strength and crack resistance of steel. The mechanism by which Mo improves tempering stability is that the addition of Mo forms a fine close-packed cubic M2X phase, which increases the secondary hardening effect. In certain reducing media, Mo can promote the passivation of Cr. Therefore, Mo can improve the corrosion resistance of martensitic stainless steel in sulfuric acid, hydrochloric acid, phosphoric acid and organic acids, and effectively inhibit the pitting tendency of chloride ions, and improve the steel's resistance to intergranular corrosion. However, Mo is expensive and should not be added too much, so the Mo content of the present invention is controlled at 0.5~1.5%.
[0041] N: N can significantly increase the yield strength of steel and increase the stability of austenite. Studies have shown that N can significantly increase the ability of pitting corrosion and crevice corrosion, mainly because N is enriched at the interface between the alloy and the passivation film, and reacts with H in the crevice. + Combined to form NH 4+ , increasing the pH value in the gap and dissolving the H near the metal ions + The consumption of N accelerates the formation of metal hydroxide, reduces the active dissolution of metal, and promotes the formation of passivation film. The N element is also beneficial to reduce the brittle σ phase and avoid affecting the mechanical properties. However, the solubility of N in molten steel is limited under normal pressure. If it is too high, the casting will produce pores and cannot be mass-produced in the factory. Therefore, the N content of the present invention is controlled at 0.05-0.15%.
[0042] The solubility of N is closely related to the solidification mode, such as the solidification mode in which ferrite is formed first and then austenite is formed during the solidification process. After the ferrite layer is solidified in the liquid phase, the ferrite lattice spacing of the bcc structure is small, and the solid solubility of N atoms is very low. This will lead to an increase in the nitrogen content in the liquid phase. When the N content in the liquid phase exceeds the N solubility, N bubbles will be generated during the solidification process. It can be seen that the precipitation of ferrite during the solidification process is not conducive to the solid solution of N atoms. Therefore, appropriately increasing austenitic elements such as Cu, Ni and Mn in alloy design is helpful to reduce the precipitation of ferrite during the solidification process, thereby increasing the N solid solubility.
[0043] Nb: The addition of Nb element can inhibit the 23 The precipitation of C6 improves the corrosion resistance of stainless steel and enhances the precipitation strengthening effect of martensitic stainless steel, thereby improving its strength and hardness. The Nb element helps to form a stable passivation film, reduce the precipitation of harmful phases, and enhance the corrosion resistance to the atmosphere and dilute acid or salt environments. It helps to control the grain growth during the hot working process, increase the start temperature and end temperature range of the hot working process, and make the hot working process more controllable. The present invention controls the Nb content to 0.01~0.1%.
[0044] In addition to the above essential elements, one or more of V≤0.20%, B≤0.0050%, and Ca≤0.0050% may be selectively added according to the desired properties, in terms of mass percentage.
[0045] V is a ferrite-forming element. Too high a V content is not conducive to the stability of austenite structure, and an upper limit control must be imposed on V. A small amount of V element can form fine VN precipitates with N, which plays a strengthening role and is beneficial to improving the strength of the material. Therefore, the V content is controlled to be ≤0.20%.
[0046] Trace amounts of B elements in stainless steel can improve the high-temperature plasticity of the material, thereby improving the processing performance. Therefore, the B content is controlled to ≤0.0050%.
[0047] Trace amounts of Ca elements in stainless steel mainly modify steelmaking inclusions, transforming inclusions with poor plasticity into inclusions with good ductility. Therefore, the Ca content is controlled to be ≤0.0050%.
[0048] The composition design features of the high-strength stainless steel of the present invention are:
[0049] 1. The present invention achieves excellent high-strength and high-plasticity mechanical properties through coordinated deformation of austenite with good plasticity and martensite with high strength in a specific ratio. The reverse-transformed metastable austenite is strengthened and toughened by deformation martensite under the action of strain during the deformation process. Studies have shown that when the reverse-transformed austenite content is between 20% and 35%, excellent strength and plasticity can be guaranteed. When the reverse-transformed austenite content is less than 20%, the strength is high, but the plasticity is poor. When the reverse-transformed austenite content is greater than 35%, the strength is low, and the plasticity is not significantly improved.
[0050] 2. The present invention regulates the tempering temperature by controlling Ms (martensite transformation starting temperature), and performs tempering at a temperature lower than Ms by 20°C, so that part of the martensite is reversely transformed into fine metastable austenite through tempering. Since the tempering temperature is lower than Ms, most of the tempered reversely transformed austenite can be retained at room temperature, thereby improving the plasticity of high-strength stainless steel;
[0051] 3. The present invention improves the pitting corrosion resistance through the Mo-N-Nb alloying design, and its pitting corrosion resistance equivalent PREN(Nb)=Cr+3.3Mo+16N+Nb≥19.0. In the PREN(Nb) formula, Cr, Mo, N and Nb elements all have a good promoting effect on the resistance to crevice corrosion. In the early stage of local corrosion development, Mo element can generate a very stable MoO2 film (about 2 to 3 times that of Cr element), which has good protectiveness and can effectively inhibit the development of corrosion. Doping N element in the Fe2O3 oxide film of stainless steel can significantly reduce the carrier concentration of the Fe2O3 oxide film (about 25 times that of Cr element), forming a negatively charged receptor center, thereby repelling Cl — ions, hindering Cl — In addition, N and Mo have a good synergistic effect in terms of crevice corrosion resistance. N can not only improve the structural strength of Cr2O3 and MoO2 oxide films, but also dissolve on the surface to generate NH4 + , which increases the pH value of the solution and causes the metal to be repassivated. The chemical reaction process is as follows:
[0052] Me+2OH - =MeO+2H2O+2e -
[0053] Secondly, the solid solubility of C in martensite is low, and Cr is easily precipitated during the cooling process. 23 C6, resulting in Cr-poor near the precipitate phase, resulting in reduced corrosion resistance. Adding Nb element can inhibit the Cr in martensite 23 C6 precipitates, thereby improving the pitting corrosion resistance. Figure 1 As shown, the PREN(Nb) value of the present invention has an obvious linear correlation with the pitting potential.
[0054] In summary, the present invention adopts a unique Mo-N-Nb alloying design, thereby having the pitting corrosion resistance of 304 stainless steel grade, ensuring excellent pitting corrosion resistance in marine environments.
[0055] The method for manufacturing the 304-grade pitting-resistant ultra-high-strength, high-plasticity, wear-resistant stainless steel of the present invention comprises the following steps:
[0056] 1) Smelting and continuous casting
[0057] According to the above chemical composition, it is smelted in blast furnace-AOD, refined in LF, and continuously cast into ingot;
[0058] 2) Hot rolling
[0059] The heating temperature of the ingot is 1200~1250℃, and the heating time is 3~4h; the ingot is rolled into plates, bars or profiles, and the final rolling temperature is 800℃~950℃. The plates, bars or profiles are quickly cooled by air cooling or water cooling, and the final cooling temperature is ≤(Ms-200), unit, ℃;
[0060] 3) Heat treatment
[0061] The hot-rolled plates, bars or profiles are directly tempered, (Ms-50)≤tempering temperature≤(Ms-20), unit, ℃.
[0062] Preferably, in step 1), during the smelting process, the reverse transformed austenite content RA is 20%≤35%.
[0063] Preferably, in step 2), the cooling rate of the hot-rolled plate, bar or profile after final rolling is ≥10°C / min.
[0064] In the manufacturing method of the present invention:
[0065] In step 1), the stainless steel composition in the smelting and continuous casting stages must satisfy the following relationship:
[0066] 20%≤Reverse transformation austenite content RA≤30%,
[0067] RA=110C+67N+2.75Ni+1.58Ni 2 -16.8Mn+4.3Mn 2 -5.6Mo-6.65.
[0068] The formula can predict that after a reasonable tempering heat treatment, the stainless steel of the present invention can produce an appropriate amount of reversed austenite, and when the RA value is 20% to 35%, an excellent combination of strength and plasticity can be obtained.
[0069] In step 2), in the cooling stage after hot rolling, the plate, bar or profile is rapidly cooled by air cooling or water cooling, and the final cooling temperature is ≤ (Ms-200), unit, ° C. Deformation dislocation strengthening is provided by hot rolling, and a large amount of martensite is formed in the matrix by the rapid cooling process, which improves the strength and provides a strength basis for the subsequent reverse transformation of austenite toughening.
[0070] Preferably, the cooling rate of air cooling or water cooling after final rolling is ≥10°C / min.
[0071] In step 3), after hot rolling and rapid cooling to room temperature, tempering heat treatment is performed, (Ms-50)≤tempering temperature≤(Ms-20), unit, ℃, at this time, martensite can form reverse austenite, because the tempering temperature is lower than Ms, it can avoid the reverse austenite from being transformed into martensite again, so that the reverse austenite can be retained to room temperature. When the tempering temperature is less than (Ms-50)℃, the reverse austenite cannot be formed because the tempering temperature is too low. When the tempering temperature is greater than (Ms-20)℃, the reverse austenite is transformed into martensite again during the cooling process after the tempering heat treatment. Both are not conducive to the formation of an appropriate content of reverse austenite.
[0072] Beneficial effects of the present invention:
[0073] 1. The present invention improves the pitting corrosion resistance through Mo-N-Nb alloying, and its pitting corrosion potential is higher than 250mV and the pitting corrosion rate is lower than 10g / (m 2 *h), the pitting corrosion resistance reaches that of 304 stainless steel (pitting potential 294mV, pitting corrosion rate 6.8g / (m 2 *h));
[0074] 2. The present invention improves the martensitic strength of the material through interstitial atomic NC alloying, and cooperates with the controlled rolling and controlled cooling + tempering heat treatment partitioning process to make the yield strength Rp0.2≥950MPa and the hardness reach above 420HBW. Compared with the long-term aging treatment of traditional precipitation hardened martensitic stainless steel, the production efficiency is greatly improved, while the precious metal alloy content is reduced, and the alloy cost and production cost are reduced;
[0075] 3. Compared with other ultra-high strength stainless steel or carbon steel, which generally have an elongation of only about 10%, the present invention forms reverse transformed austenite through tempering treatment. These metastable austenites undergo deformation martensite toughening effect during the deformation process, which increases the elongation to more than 15%.
[0076] In summary, the comparison of the corrosion resistance and mechanical properties of the present invention with 304 austenitic stainless steel and Hardox450 wear-resistant steel is shown in Table 1. The present invention has the characteristics of corrosion resistance, high strength, high wear resistance and good plasticity.
[0077] Table 1
[0078] Steel Type Corrosion resistance strength Plasticity Wear resistance The present invention excellent excellent good excellent Hardox450 Difference excellent Difference excellent 304 excellent Difference excellent Difference BRIEF DESCRIPTION OF THE DRAWINGS
[0079] Figure 1 The correlation between the finished product PREN (Nb) of the present invention and the pitting potential;
[0080] Figure 2 It is a metallographic photograph of the finished product of the present invention;
[0081] Figure 3 EBSD phase distribution diagram of hot-rolled state and different tempering temperatures of Example 6 of the present invention. DETAILED DESCRIPTION
[0082] The present invention will be further described below in conjunction with the embodiments and drawings.
[0083] The chemical compositions of the embodiments and comparative examples of the present invention are shown in Table 2, and the balance includes Fe and other inevitable impurity elements. The manufacturing process parameters of the embodiments and comparative examples are shown in Table 3. The performance results of the embodiments and comparative examples are shown in Table 4.
[0084] like Figure 2 As shown, the microstructure of the stainless steel of the present invention is martensite+austenite.
[0085] Compared with Examples 1 to 8, the pitting rate and pitting potential of Comparative Example 1 are shown in Table 4. When the PREN(Nb) value is lower than 19.0, the pitting resistance is significantly reduced, and the pitting potential cannot be higher than 250mV and the pitting rate is lower than 10g / (m 2 *h) Corrosion performance requirements.
[0086] Compared with Example 8, the main alloying elements in Comparative Example 2 are basically the same, but no Nb element is added, resulting in Cr 23 C6 precipitates at the grain boundaries, reducing the corrosion resistance of the material.
[0087] In Comparative Example 3, the calculated RA value of the reversed austenite content is less than 20%. After tempering heat treatment, the reversed austenite content is insufficient, resulting in poor plasticity and an elongation of only 10.3%.
[0088] In Comparative Example 4, the calculated RA value of the reversed austenite content is higher than 30%. After tempering heat treatment, the reversed austenite content is too high, resulting in lower strength and plasticity.
[0089] In Comparative Example 5, the tempering temperature is higher than Ms, resulting in that the formed reverse transformed austenite is transformed into martensite again during the cooling process, resulting in insufficient plasticity and an elongation of 11.6%.
[0090] In Comparative Example 6, the tempering temperature was 50°C lower than Ms, resulting in failure to form reversed austenite during the tempering heat treatment, resulting in insufficient plasticity and an elongation of 9.5%.
[0091] In Comparative Example 7, the cooling rate of the hot-rolled plate is 810°C / min, which is lower than 10°C / min, resulting in a high content of retained austenite and insufficient strength.
[0092] The above embodiments and comparative examples illustrate that only qualified stainless steel products can be obtained according to the composition design and process parameters described in the present invention.
[0093] It can be seen from Table 4 that the present invention has excellent pitting corrosion resistance: the pitting corrosion rate of Examples 1 to 8 is less than 10 g / (m 2 *h), the pitting potential is higher than 250mV, and the pitting resistance is equivalent to that of 304 stainless steel.
[0094] Table 5 shows the mechanical properties and reversed austenite content of Example 6 of the present invention in the hot-rolled state and at different tempering temperatures.
[0095] After hot rolling, the steel is rapidly cooled to room temperature and then subjected to tempering heat treatment. The tempering temperature is 20~50℃ below Ms. At this time, martensite can form reversed austenite. Since the tempering temperature is lower than Ms, the reversed austenite can be prevented from transforming into martensite again, so that the reversed austenite can be retained to room temperature.
[0096] The distribution of the reversed austenite of the sample in hot-rolled state and after tempering at different temperatures in Example 6 is as follows: Figure 3 As shown, red represents martensite and blue represents reversed austenite. The hot-rolled sample of Example 6 contains a small amount of blocky residual austenite. When the tempering temperature is 300°C, reversed austenite cannot be formed due to the low temperature. The Ms temperature of Example 6 is 470°C. When the tempering temperature is 400°C and 450°C, the content of blocky austenite shown in blue is significantly increased. It can be seen that 20~50°C below Ms is the austenite reverse transformation temperature range of the present invention. When the temperature is raised to 500°C, the reversed austenite is further reduced, which indicates that the reversed austenite is transformed into martensite again during the tempering cooling process.
[0097] The mechanical properties and reversed austenite content of the hot-rolled plate of Example 6 after being treated at different tempering temperatures are shown in Appendix 5. When (Ms-50)≤tempering temperature≤(Ms-20), unit, ℃, the reversed austenite content is high and the elongation can be close to 20%, while at other tempering temperatures, the reversed austenite content is small and the plasticity is insufficient.
[0098] The stainless steel of the present invention has excellent mechanical properties: the yield strength of the example steel is higher than 950 MPa, the elongation is about 15-20%, and the hardness is higher than 420 HBW. Its yield strength and hardness are equivalent to Hardox450 steel, but its elongation is much higher than Hardox450 steel.
[0099] Table 2 Unit: Mass percentage
[0100] C Si Mn P S Cr Ni Mo N Nb V B Ca Example 1 0.037 0.354 2.52 0.034 0.0013 14.13 4.18 1.08 0.096 0.050 0.07 0.0041 0.0015 Example 2 0.142 0.423 1.13 0.032 0.0010 14.29 3.59 1.23 0.056 0.045 0.12 0.0004 0.0028 Example 3 0.069 0.923 2.34 0.033 0.0014 14.69 3.80 0.57 0.098 0.098 0.11 — 0.0048 Example 4 0.071 0.255 2.96 0.032 0.0012 14.36 3.31 0.73 0.133 0.020 0.19 0.0023 0.0035 Example 5 0.110 0.503 1.26 0.037 0.0013 15.86 3.94 0.68 0.076 0.045 0.02 0.0014 0.0010 Example 6 0.031 0.621 1.82 0.032 0.0011 14.59 4.86 1.25 0.054 0.075 — 0.0049 0.0018 Example 7 0.105 0.436 2.33 0.041 0.0011 14.31 4.44 1.48 0.069 0.081 0.15 0.0035 — Example 8 0.078 0.492 1.98 0.025 0.0012 15.48 3.78 0.55 0.141 0.028 0.07 0.0039 0.0030 Comparative Example 1 0.045 0.398 2.67 0.032 0.0014 14.23 4.05 0.58 0.068 0.022 0.18 0.0028 0.0012 Comparative Example 2 0.074 0.468 1.81 0.036 0.0010 15.52 3.71 0.59 0.142 — 0.11 0.0023 0.0021 Comparative Example 3 0.042 0.422 1.46 0.032 0.0012 14.98 3.35 0.61 0.099 0.049 0.05 0.0015 0.0021 Comparative Example 4 0.096 0.456 1.46 0.031 0.0013 14.68 4.55 0.61 0.112 0.046 0.10 0.0031 0.0028 Comparative Example 5 0.077 0.502 2.39 0.033 0.0012 14.68 3.74 0.75 0.105 0.068 0.12 0.0019 0.0014 Comparative Example 6 0.077 0.502 2.39 0.032 0.0011 14.68 3.74 0.75 0.105 0.068 0.12 0.0029 0.0016 Comparative Example 7 0.105 0.436 2.33 0.041 0.0011 14.31 4.44 1.48 0.069 0.081 0.15 0.0035 0.0001
[0101] Table 3
[0102] PREN(Nb) RA% Ms℃ Tempering temperature℃ Billet heating temperature ℃ Slab heating time h Finishing rolling temperature℃ Cooling speed℃ / min Example 1 19.83 21.88 462.94 441 1205 3.5 915 16 Example 2 19.79 22.58 492.78 453 1220 3.3 886 21 Example 3 19.32 21.81 447.03 420 1215 3.9 812 13 Example 4 19.14 20.34 440.15 412 1235 3.6 836 26 Example 5 19.86 27.75 447.47 424 1245 3.1 868 18 Example 6 20.48 27.73 470.73 450 1225 3.2 941 27 Example 7 21.27 28.79 441.11 401 1240 3.4 906 31 Example 8 19.89 24.86 429.03 400 1220 3.6 889 19 Comparative Example 1 17.50 22.46 469.38 440 1230 3.5 916 22 Comparative Example 2 19.75 23.33 436.42 402 1221 3.4 845 25 Comparative Example 3 19.17 12.77 490.39 460 1246 3.2 829 21 Comparative Example 4 19.04 37.86 458.31 430 1227 3.8 876 13 Comparative Example 5 19.65 21.45 445.86 500 1210 3.4 859 15 Comparative Example 6 19.65 21.45 445.86 350 1238 3.6 904 18 Comparative Example 7 21.27 28.79 441.11 423 1226 3.2 895 8
[0103] Table 4
[0104] Pitting potential (mV) <![CDATA[Pitting corrosion rate g / (m 2 *h)]]> Yield strength(MPa) Tensile strength(MPa) Elongation(%) Hardness(HBW) Example 1 288 6.32 1062 1398 18.7 452 Example 2 289 6.69 1093 1443 19.4 448 Example 3 274 8.65 1068 1412 17.6 456 Example 4 271 8.25 1020 1396 18.3 442 Example 5 281 7.24 1035 1428 20.8 445 Example 6 298 6.28 1043 1408 19.6 442 Example 7 312 5.45 1010 1432 19.5 442 Example 8 286 6.12 1040 1421 19.6 453 Comparative Example 1 234 11.36 1035 1411 18.3 439 Comparative Example 2 213 14.68 986 1335 18.6 435 Comparative Example 3 273 8.37 1069 1345 10.3 443 Comparative Example 4 277 8.69 864 1385 9.3 456 Comparative Example 5 281 7.96 1063 1396 11.6 449 Comparative Example 6 283 8.23 993 1375 9.5 432 Comparative Example 7 308 6.42 768 1286 9.1 403 Hardox450 / / 1076 1406 10.6 448 304 297 7.68 296 712 57.5 164HV
[0105] Table 5
[0106] State of Steel Yield strength / MPa Tensile strength / MPa Elongation / % Reverse transformation austenite content / % Hot Rolling 639 1253 9.8 2.5 300℃-0.5h 1003 1465 11.2 4.1 400℃-0.5h 1066 1380 18.0 25.9 450℃-0.5h 1067 1376 21.4 29.7 500℃-0.5h 1069 1439 10.8 4.7 550℃-0.5h 757 1389 13.3 0.1
Claims
1. 304 grade ultra-high strength, high plasticity, wear-resistant stainless steel with pitting resistance, its chemical composition mass percentage is: C:0.03~0.15%, Si: 0.25~1.0%, Mn: 1.0~3.0%, Cr:14.0~16.0%, Ni: 3.0~5.0%, Mo: 0.5~1.5%, N:0.05~0.15%, Nb: 0.01~0.1%, P≤0.045%, S≤0.0020%, The balance is Fe and other unavoidable impurities, and the following relationship must be satisfied at the same time: Pitting resistance equivalent PREN (Nb) ≥ 19.0, Pitting resistance equivalent PREN (Nb) = Cr + 3.3Mo + 16N + Nb; 20%≤Reverse transformation austenite content RA≤35%, RA=110C+67N+2.75Ni+1.58Ni 2 -16.8Mn +4.3Mn 2 -5.6Mo-6.65, unit, volume percentage; 400℃≤Martensite transformation Ms≤500℃, Ms = 1050-301 (C + N) -33.3Mn-28Cr-16.7Ni-11.1 (Mo + Si) -35 × Nb, unit, °C; The yield strength Rp of the stainless steel 0.2 ≥950MPa, elongation EL≥15%, hardness ≥420HBW, pitting potential ≥250mV, pitting rate ≤10 g / (m 2 *h).
2. The 304 grade pitting-resistant ultra-high strength, high plasticity, wear-resistant stainless steel according to claim 1, characterized in that: The chemical composition of the stainless steel further includes: one or more of V≤0.2%, B≤0.0050%, and Ca≤0.0050%, in mass percentage.
3. The 304 grade pitting-resistant ultra-high strength, high plasticity, wear-resistant stainless steel according to claim 1 or 2, characterized in that: The microstructure of the stainless steel is martensite+austenite.
4. The method for manufacturing the 304 grade pitting corrosion resistant ultra-high strength, high plasticity and wear-resistant stainless steel according to any one of claims 1 to 3, characterized in that: The steps include: 1) Smelting and continuous casting According to the chemical composition of claim 1 or 2, blast furnace-AOD smelting, LF refining, and continuous casting into ingots; during the smelting process, 20%≤RA≤35% is controlled; 2) Hot rolling The heating temperature of the ingot is 1200~1250℃, and the heating time is 3~4h; the ingot is rolled into plates, bars or profiles, and the final rolling temperature is 800℃~950℃. The plates, bars or profiles are quickly cooled by air cooling or water cooling, and the cooling rate is ≥10℃ / min; the final cooling temperature is ≤(Ms-200), unit, ℃; 3) Heat treatment The hot-rolled plates, bars or profiles are directly tempered, (Ms-50)≤tempering temperature≤(Ms-20), unit, ℃.
Citation Information
Patent Citations
Tough ultra-strength stainless steel and method for manufacturing the same
CN101205595B
Ultrahigh-strength stainless steel with good plasticity and ductility and manufacturing method thereof
CN102605279A
Wear-resistant stainless steel as well as preparation method and workpiece thereof
CN117987740A
High strength super-martensitic stainless steel for oil and gas pipelines and preparation method thereof
CN101956146A